Heme oxygenase-1 modulates CD62E-dependent endothelial cell-monocyte interactions and mitigates HLA-I-induced transplant vasculopathy in mice - Schuster, Laura; Zaradzki, Marcin; Janßen, Henrike; Gallenstein, Nadia; Etheredge, Melanie; Hofmann, Ilse; Weigand, Markus A.; Immenschuh, Stephan; Larmann, Jan (Frontiers in immunology, 2025)
The main risk factor for developing transplant vasculopathy (TV) after solid organ transplantation is de-novo production of donor-specific antibodies (DSAs) binding to endothelial cells (ECs) within the graft's vasculature. Diverse leukocyte populations recruited into the vessel wall via activated ECs contribute to vascular inflammation. Subsequent smooth muscle cell proliferation results in intima hyperplasia, the pathophysiological correlate of TV. We demonstrated that incubating aortic EC with anti-HLA-I antibodies led to increased monocyte adhesion to and transmigration across an EC monolayer. Both occurred in a CD62E-dependent fashion and were sensitive toward the anti-inflammatory enzyme heme oxygenase (HO)-1 modulation. Using a murine heterotopic aortic transplantation model, we demonstrated that anti-MHC I antibody-induced TV is ameliorated by pharmacologically induced HO-1 and the application of anti-CD62E antibodies results in a deceleration of developing TV. HO-1 modulation is a promising therapeutic approach to prevent leukocyte recruitment and subsequent intima hyperplasia in TV and thus precludes organ failure.
Gesehen am 30.10.2025